Interpretasi Pengguna Tiktok Terhadap Konten Willie Salim - M. Tsalits Amalil Fauzy; Alwan Abdillah Asa; Raffi Dwinanda Hartoni; M. Khibrah Aufa Firdaus; Rio Kurniawan (Universitas Sunan Drajat Lamongan, Indonesia, 2025)
As TikTok’s popularity increases, so do content creators who have a big influence on the platform. One of them is Willie Salim, a content creator known for his social content such as giving away money, positive pranks, and surprise actions. This kind of content gets wide attention from the public because it is considered to touch the emotional side of the audience and provide a narrative of goodness wrapped in entertainment. This study aims to understand how TikTok users interpret content produced by Willie Salim, a content creator known for his social actions on social media. Using a qualitative approach with a phenomenological method, this study collected data through in-depth interviews and content observations to explore the subjective experiences of the audience in interpreting the meaning of the videos displayed. The results of the study show that interpretations of Willie Salim’s content vary widely. Some users interpret it as inspiration and a form of social concern, while others assess it critically, seeing elements of image building or exploitation for the sake of popularity. These findings confirm that the audience has an active role in interpreting media messages based on their respective backgrounds and experiences. This research contributes to the study of digital mass communication, especially in understanding how public perception is formed in the era of social media, and becomes a reference for content creators in understanding audience responses to their work.